Redescription of Barilius ornatus Sauvage (Cypriniformes: Cyprinidae) with data from a population from the eastern part of the Isthmus of Kra, Thailand - Tejavej, Anuratana (Zootaxa, 2012)
Barilius ornatus, the first described species of Barilius from Southeast Asia, is redescribed with data from additional spec-imens from the eastern part of the Isthmus of Kra. The species is characterized by having 37–40 scales (rarely 36) alongthe lateral line, 6–7scale rows above the lateral line, 17–20 (rarely 16 or 21) predorsal scales, 12–14 circumpeduncularscales, anal-fin origin opposite from the 6th branched dorsal-fin ray to behind the last branched dorsal-fin ray, head depth17–21% SL, predorsal length not more than 58% SL, dark pigment on dorsal fin concentrated at the edge of the brancheddorsal-fin rays, generally short and thin rostral and maxillary barbels (if present), 1–2 small caudal spots or no caudal spot,and small dentary tubercles. With data from additional specimens B. ornatus can be clearly differentiated from Bariliusbarnoides Vinciguerra and Barilius infrafasciatus Fowler. The status of Barilius caudiocellatus Chu, and Barilius barila Hamilton are also discussed.